Forest soil carbon oxidation state and oxidative ratio responses to elevated CO2. Issue 9 (21st September 2015) - Hockaday, William C.; Gallagher, Morgan E.; Masiello, Caroline A.; Baldock, Jeffrey A.; Iversen, Colleen M.; Norby, Richard J.
Abstract: The oxidative ratio (OR) of the biosphere is the stoichiometric ratio (O2 /CO2 ) of gas exchange by photosynthesis and respiration—a key parameter in budgeting calculations of the land and ocean carbon sinks. Carbon cycle‐climate feedbacks could alter the OR of the biosphere by affecting the quantity and quality of organic matter in plant biomass and soil carbon pools. This study considers the effect of elevated atmospheric carbon dioxide concentrations ([CO2 ]) on the OR of a hardwood forest after nine growing seasons of Free‐Air CO2 Enrichment. We measured changes in the carbon oxidation state (Cox ) of biomass and soil carbon pools as a proxy for the ecosystem OR. The OR of net primary production, 1.039, was not affected by elevated [CO2 ]. However, the Cox of the soil carbon pool was 40% higher at elevated [CO2 ], and the estimated OR values for soil respiration increased from 1.006 at ambient [CO2 ] to 1.054 at elevated [CO2 ]. A biochemical inventory of the soil organic matter ascribed the increases in Cox and OR to faster turnover of reduced substrates, lignin and lipids, at elevated [CO2 ]. This implicates the heterotrophic soil community response to elevated [CO2 ] as a driver of disequilibrium in the ecosystem OR. The oxidation of soil carbon pool constitutes an unexpected terrestrial O2 sink. Carbon budgets constructed under the assumption of OR equilibrium would equate such a terrestrial O2 sink to CO2 uptake by the ocean. The potential for climate‐driven disequilibriua in the cycling of O2 and CO2 warrants further investigation. Key Points: Soil carbon oxidation state increased with atmospheric CO2 concentration The carbon oxidation state is sensitive to disequilibria in O2 and CO2 fluxes Hardwood forests may be an atmospheric O2 sink at high CO2 levels